Efektifitas Hypnobreastfeeding Pada Ibu Menyusui Terhadap Kecukupan Asi Pada Bayi Usia ≤ 3 Bulan Di Praktik Mandiri Bidan Risma Dan Praktik Mandiri Bidan Sri Armila Deli Serdang Tahun 2018 - Rismahara Lubis; Yusniar Siregar; Evi Irianti (Universitas Muhammadiyah Sumatera Utara, 2020)
Some of mothers who experiences of obstacles breastfeeding their babies exclusively for 6 months fully and hypnobreastfeeding is one of solution. The purpose of this study was to determine the effectiveness of hypnobreastfeeding on mothers keep on the adequacy of breast milk in infant ages 3 months at Independent Midwives Practices “Risma” and Independent Midwife Practices “Sri Armila” Deli Serdang in 2018. This research is an experimental Quasi. The sample size is 32 postpartum mothers who exclusively breastfeeding their babies, devided two groups as control and experiment. Data be analized by Kruskal Wallis test with a significance level of 0.05. The result is found significant differences increasing infant weight between control and treatment groups ranging from 1 to 3 ages months. There is a significant difference of urinary frequence between control and treatment group from the first day birthing till 3 months up. Keywords: Hypnobreastfeeding, breastfeeding adequacy, babies aged ≤3months